Raw data to peat cosm analysis from the Meadowlands in Minnesota, USA - Evan S Kane (PANGAEA, 2019)
Globally important carbon (C) stores in northern peatlands are vulnerable to oxidation in a changing climate. A growing body of literature draws attention to the importance of dissolved organic matter (DOM) in governing anaerobic metabolism in organic soil, but exactly how the reduction-oxidation (redox) activities of DOM, and particularly the phenolic fraction, are likely to change in an altered climate remain unclear. We used large mesocosms in the PEATcosm experiment to assess changes in peatland DOM and redox potential in response to experimental manipulations of water table (WT) position and plant functional groups (PFGs). WT position and PFGs interacted in their effects on redox potential and quantity and quality of DOM. Phenolics were generally of higher molecular weight and more oxidized with sedges in lowered water tables. Altered DOM character included changes in dissolved nitrogen (N), with higher N:phenolics with higher E4:E6 (absorbance ratio = 465:665) DOM in the lowered WT and sedge PFG treatments. Conversely, biomolecular assignments to free amino-sugars were largely absent from low WT treatments. Drainage resulted in the creation of unique N compounds which were more condensed (lower H:C), that changed with depth and PFG. The accumulation of oxidized compounds with low WT and in sedge rhizospheres could be very important pools of electron acceptors beneath the water table, and their mechanisms of formation are discussed. This work suggests the effects of changes in vegetation communities can be as great as WT position in directly and interactively mediating peat redox environment and the redox-activity of DOM.
Supplement to: Kane, Evan S; Veverica, T J; Tfaily, Malak M; Lilleskov, Erik A; Meingast, Karl M; Kolka, Randall K; Daniels, Aleta L; Chimner, Rodney A (2019): Reduction-oxidation potential and dissolved organic matter composition in northern peat soil: interactive controls of water table position and plant functional groups. Journal of Geophysical Research: Biogeosciences, https://doi.org/10.1029/2019JG005339